Distribution and persistence of residual T-2 and HT-2 toxins from moldy feed in broiler chickens. (30th April 2020) - Yang, Lingchen; Tu, Di; Wu, Yingxin; Liu, Wei; Hu, Yi; Liu, Tanbin; Tan, Lei; Li, Yalan; Lei, Hongyu; Zhan, Yang; Wang, Naidong; Deng, Zhibang; et al.
Abstract: T-2 and HT-2 widely found in food products can seriously affect human and animal health. In this study, sterilized corn was inoculated with F. poae and incubated to allow fungal growth before being examined via liquid chromatography coupled to tandem mass spectrometry (HPLC-MS/MS) to determine the concentrations of T-2/HT-2. Broilers were then fed with a mix of moldy corn and normal feed at different ratios to obtain different toxin doses. After 35 days, the contaminated feed was replaced with mycotoxin-free feed and the distribution and concentration of residual toxins in the tissues and organs of the chickens were examined at different time points. The results showed that at the time of feed replacement (0 h), T-2 residue was present at significantly higher concentrations in the lungs and small intestines than in other tissues ( P  < 0.05). In addition, T-2 concentrations increased in a dose-dependent manner in the tissues of chickens in the low-, medium-, and high-dose groups; however, the differences in concentration between the groups were not statistically significant. The HT-2 content (0 h) in the livers and small intestines was significantly higher than that in other tissues ( P  < 0.05). At 48 h post-feed replacement, the concentration of T-2 dropped below detectable levels in all tissues while HT-2 could still be detected at 192 h post-feed replacement. Thus, this study reveals the distribution and persistence of residual T-2/HT-2 from moldy feed in broilers, providing a reference for the detection of these toxins in animal-derived food products and a theoretical basis for formulating food-safety and quality standards. Highlights: We obtained high levels of T-2/HT-2 produced by maize incubated with F. poae instead of pure toxins. T-2 and HT-2 were distributed in biological matrices of broilers after ingestion of moldy feed. Residual T-2 and HT-2 was still in tissues 48 h and 192 h post-cessation of feeding with contaminated corn, respectively.